Gender Representation in Narrative Texts of Elementary School Indonesian Language Textbooks in the Merdeka Curriculum - Elsa Rahmalia Putri; Nadia Tiara Antik Sari; Neneng Sri Wulan (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
Textbooks in elementary education function not only as learning resources but also as media that shape students’ understanding of gender roles through the representation of characters, activities, and social interactions. However, studies on gender representation in narsrative texts of Indonesian language textbooks under the Merdeka Curriculum remain limited, particularly those examining character positions, identity roles, interaction roles, and activity spaces simultaneously. Therefore, this study aimed to analyze gender representation in narrative texts contained in Grades IV–VI Indonesian language textbooks of the Merdeka Curriculum. This study employed a qualitative content analysis approach. The data consisted of 38 narrative texts analyzed using a coding sheet adapted from the gender representation framework of Brugeilles and Cromer (2009). Data were analyzed through data reduction, data display, and conclusion drawing. The findings show that gender representation varies across grade levels. Grade IV texts are characterized by male dominance, particularly in public activities, whereas female characters are more frequently associated with domestic activities. Grade V texts demonstrate a more balanced pattern through increased female participation in educational activities and social interactions. Grade VI texts present a more inclusive representation, with female characters appearing more frequently as main characters and in educational, social, and leadership roles. Overall, the findings indicate a gradual shift toward more inclusive gender representation across grade levels, although traditional gender stereotypes remain evident in the distribution of activities, roles, and activity spaces.